Kontribusi Tafsir Al-Jami’ Li Ahkam Al-Qur’an Karya Imam Al-Qurtubi Terhadap Perkembangan Ilmu Fiqih - Azizah (Prodi Ilmu Al Qur'an dan Tafsir, 2026)
Abstract This research stems from the vital role of the book Al-Jami‘ li Aḥkam al-Qur’an by Al-Qurtubi as one of the primary references in interpreting the legal verses of the Qur'an, which has significantly influenced the development of Islamic jurisprudence (fiqh). This exegesis (tafsir) serves as an important representation of the Andalusian intellectual tradition and remains highly relevant in contemporary Islamic legal discourse. This study employs a qualitative method with a library research approach. The primary source of this research is the book Al-Jami‘ li Aḥkam al-Qur’an, while the secondary sources include various relevant academic literature, articles, and scientific works. The data were analyzed using reduction techniques and thematic interpretation to uncover the strengths and contributions of Al-Qurtubi's tafsir to the development of fiqh and Islamic law, as well as to reveal Al-Qurtubi's biography and the background of the text's composition. The results indicate that Al-Qurtubi's tafsir is characterized by a jurisprudential (fiqhi) legal nuance utilizing the analytical (tahlili) method, systematically combining both traditional narration (riwayah) and rational opinion (ra'yi). The superiority of this tafsir lies in its depth of legal analysis, objectivity toward differences among school of thoughts (mazhab), and its contribution to strengthening the foundations of classical and contemporary Islamic law. Thus, this work stands as an authoritative and relevant Islamic intellectual heritage for the development of modern Islamic legal thought. Keywords: Contribution, Al-Jami’ Li Ahkam Al-Qur’an, Jurisprudence (Fiqh)